The Effect Of Government Spending For Economic Structure Changes In Gorontalo Province - Dyna Pratama Gobel; Fitri Hadi Yulia Akib (Jambura Equilibrium Journal, 2019)
This study aims to determine the extent of the effect of government spending on changes in economic structure in Gorontalo Province 2011-2016. This study uses panel data regression analysis, with quantitative descriptive methods. and to calculate the shift in structure in Gorontalo Province using the formula (Structural Change Index). The results showed that Government spending directed at economic development in the Province of Gorontalomen showed a positive effect, meaning that the role of the primary sector was increasing so that it did not have an impact on changes in economic structure. Keywords: Government Spending, Economic Structural Change